Nærværets moral i distansenes verden (Sociologisk Forskning, 1998)
The morality of closeness in a world of distancesThis article addresses the potentials and hindrances of moral relationships in contemporary world society, as they increasingly are mediated through modern mass media. Of particular interest is Levinasian ethics of responsibility stemming from the face of the Other. It particularly discusses the postmodern version of such ethics as it has been interpreted and developed sociologically by Zygmunt Bauman. The essay consists of three parts: First, the image of a post-ethical world in the media is interpreted through the perspective of Bauman. Second, the question discussed is whether the Other can be morally perceived through the mediation of modern technical media, particularly television. Third, the dilemma of the appearance of the Third is discussed: Can a levinasian ethics be a macro-ethics? Generally, the essay constitutes a critical comment to Bauman’s far-reaching ambitions on behalf of anethics of closeness.